2014
DOI: 10.1021/ol503364w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Spiropseudoindoxyls via an Intramolecular Nitroalkyne Redox–Dipolar Cycloaddition Cascade

Abstract: Novel spiropseudoindoxyls were synthesized in high yields via a fully regioselective Au(III)-catalyzed cycloisomerization of easily obtainable o-nitrophenylpropiolamides, followed by an intramolecular dipolar cycloaddition as key steps. This one-pot cascade reaction resulted in new tetracyclic pseudoindoxyls, which were hydrogenated toward the title compounds as single diastereomers via N-O cleavage. The mechanism of the gold catalyzed cycloisomerization was studied by DFT and suggests a reaction path without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…While various spiropseudoindoxyls 4 were now readily available, they were still all constrained by an isoxazolidine moiety. As previously reported, this ring can be opened by hydrogenation of the N−O bond. For the tosylated substrates 4 b and 4 q , only one diastereomer was isolated in good yields ( 13 a and 13 c ; Scheme ).…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…While various spiropseudoindoxyls 4 were now readily available, they were still all constrained by an isoxazolidine moiety. As previously reported, this ring can be opened by hydrogenation of the N−O bond. For the tosylated substrates 4 b and 4 q , only one diastereomer was isolated in good yields ( 13 a and 13 c ; Scheme ).…”
Section: Methodssupporting
confidence: 60%
“…These reactions afford a-oxo amide carbenoids (or related stabilized cations), which can be used in the synthesis of various heterocycles. [6] Several of these 2-spirocyclic fused 1,2-dihydroindol-3-ones (also named spiropseudoindoxyls) display ab road range of bioactivities and often originate from indole alkaloids after oxidation-induced ring contractions. [5] In previous work by our group and others,the reactivity of ortho-nitrophenylpropiolamides or related compounds in the presence of ag old catalyst was investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel to our report, Verniest's group reported a similar Au(III)-catalysed cycloisomerization of o-nitrophenyl-propiolamides 98 and subsequent intramolecular dipolar cycloaddition with alkenes afforded the tetracyclic core (Scheme 21). [31] The strained heterocycle underwent NÀ O bond reduction by hydrogenative cleavage, which provided the tricyclic C2spiropseudoindoxyl product 99 as a single diastereomer. Interestingly, DFT studies revealed that these transformations do not involve the gold carbene 98-B.…”
Section: Cascade Transformations By Combining the [Au]-catalysed Nitralkyne Cycloisomerization With Cycloaddition Reactionsmentioning
confidence: 99%
“…[1] For instance, the mitragynine pseudoindoxyl [1g-h] and brevianamide A [1i] exhibited strong opioid agonistic activity and insecticidal activity, respectively. Driven in part by their plentiful biological activities and intriguing architectures, numerous synthetic approaches toward these compounds, such as oxidative rearrangement of indole derivatives, [2] Smalley cyclization, [3] cycloisomerization of nitroalkynes, [4] Ugi reactions, [5] and others [6] have been successfully developed in the past several decades. However, catalytic asymmetric reactions have scarcely been reported likely due to the great challenge in the creation of the spirocyclic quaternary stereogenic carbon center, despite the fact that the resulting enantioenriched products might be helpful in drug discovery.…”
mentioning
confidence: 99%